2019
DOI: 10.1007/978-3-030-17705-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Chasing the Chatbots

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Additionally, our findings suggest that any chatbot system should comply with several principles or rules that various authors already pointed out (Amato et al, 2017;Moore, 2018;Piccolo et al, 2019;Tavanapour et al, 2019). Chatbots should manage the unexpected by keeping the context, the coherence, and the conversation flow; have the capacity of summarisation but also to repair, repeat or paraphrase; recognise user utterances and preferences; provide affective, emotional and social cues; may be entertaining; must be transparent and provide trustfulness.…”
Section: Suggestions For Engaging Citizenssupporting
confidence: 63%
“…Additionally, our findings suggest that any chatbot system should comply with several principles or rules that various authors already pointed out (Amato et al, 2017;Moore, 2018;Piccolo et al, 2019;Tavanapour et al, 2019). Chatbots should manage the unexpected by keeping the context, the coherence, and the conversation flow; have the capacity of summarisation but also to repair, repeat or paraphrase; recognise user utterances and preferences; provide affective, emotional and social cues; may be entertaining; must be transparent and provide trustfulness.…”
Section: Suggestions For Engaging Citizenssupporting
confidence: 63%
“…The recent substantial increase in chatbot research can be seen as a direct response to the uptake of so-called virtual assistants by big tech companies, specifically the inclusion of Siri as part of Apple operating system in 2011, Amazon's promotion of Alexa since 2014 and the conversational turn of Facebook, Microsoft and Google in 2016 [25]. Piccolo et al [86] concluded that chatbot research has followed in the trail of the industrial uptake of conversational computer systems rather than being at the driver seat. In consequence, the contribution of this burgeoning research area is as much to understand the emerging application, uses, and implications of conversational computing systems, as to improve on their technological underpinnings and methods for design and development.…”
Section: Historical Roots Of Chatbot Researchmentioning
confidence: 99%
“…Chatbots are currently taken up in application areas as diverse as customer service [1], health [105], education [53], and office work [78]. There has lately been a marked increase of interest in chatbot research within academia and industry, specifically from 2016 and onwards [86]. Recent research addresses, for example, chatbot use (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Additional areas of improvement for existing chatbots can be found in the dimensions of socio-emotional behavior and personality processing, where most of the analyzed chatbots present limited capabilities, while research has progressed significantly. Users expect chatbots to have human-like communication skills, which implies that not only chatbot personality, but also conversational style and socio-emotional skillset need to be adapted to the domain, end-user, and platform for which a chatbot has been designed (Jain et al 2018;Piccolo et al 2018). The area of emotional processing is currently being studied in the scientific community from various perspectives.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Although some elemental chatbot classification frameworks can be found in scientific literature, the research is dispersed into different thematic axes and research areas. Furthermore, the scientific and practical knowledge about chatbots has also grown in a segregated manner given a shortage of integrative perspectives to support chatbot development and design processes Jain et al 2018;Piccolo et al 2018). For instance, most scientific studies today concentrate on particular aspects of chatbots, such as the personality of cognitive chatbots, technical capabilities or their specific application Accepted after three revisions by the editors of the Special Issue.…”
Section: Introductionmentioning
confidence: 99%